Epigenetic mechanisms in alcohol- and adversity-induced developmental origins of neurobehavioral functioning - Boschen, KE (Neurotoxicol Teratol, 2018)
The long-term effects of developmental alcohol and stress exposure are well documented in both humans and non-human animal models. Damage to the brain and attendant life-long impairments in cognition and increased risk for psychiatric disorders are debilitating consequences of developmental exposure to alcohol and/or psychosocial stress. Here we discuss evidence for a role of epigenetic mechanisms in mediating these consequences. While we highlight some of the common ways in which stress or alcohol impact the epigenome, we point out that little is understood of the epigenome’s response to experiencing both stress and alcohol exposure, though stress is a contributing factor as to why women drink during pregnancy. Advancing our understanding of this relationship is of critical concern not just for the health and well-being of individuals directly exposed to these teratogens, but for generations to come.